Sistem Informasi Pengadaan Peralatan dan Perlengkapan Kantor pada Dinas Kehutanan Propinsi Riau Berbasis Web - Yuda Irawan (Puslitbang Sekawan Institute Nusa Tenggara, 2019)
In the development of increasingly advanced and sophisticated technology, tools are needed that help facilitate a job, one of which is a computer. Computers are the main choice in the progress of agencies in general because an agency aims to maximize agencies can grow and develop as expected. Designing Procurement Information Systems for Web-Based Office Equipment and Supplies is to provide complete information about Procurement of Office Equipment, Procurement Information Systems Equipment and Office Supplies at Riau Province Forestry Services Using PHP and MySQL database is a software that can be used to process equipment data office where transaction reports for ATK request transactions, ATK stock reduction can be known every day automatically if all transactions have been sent to the system. Thus work from the Finance and Equipment Section can be helped and will make time effective